Brief on scaling the youth and women quality centre model for Inclusive seed systems in Uganda - Lutomia, Cosmas Kweyu; Bomuhangi, Allan; Yila, Jummai Othniel; Ketema, Dessalegn; Nchanji, Eileen (2025)
Smallholder farmers in Uganda—particularly women and youth—continue to rely heavily on informal seed systems, with certified seed representing only a small fraction of planting material. This constrains productivity, limits access to improved varieties and restricts economic opportunities for young people and women in key value chains such as rice and common beans. To address these challenges, the International Rice Research Institute (IRRI), the Alliance of Bioversity International and CIAT, and partners co-designed and piloted the Youth and Women Quality Centre (YWQC) model in Butaleja District as a locally embedded, gender-responsive approach to strengthening inclusive seed systems YWQCs function as community-based hubs that combine technical training, business incubation, behavioural change communication, and market and f inance linkages. They deliberately position youth and women not only as beneficiaries, but also as seed producers, service providers, and agribusiness actors. Evidence from baseline and endline surveys covering over 700 rice and bean farmers shows that the model has delivered substantial gains. Access to improved bean varieties rose from about 42% to over 90% of farmers, while improved rice adoption increased from 61% to 93%. Importantly, gender gaps in access narrowed or reversed, and youth participation and productivity matched or exceeded that of older farmers. The YWQC model also reshaped seed sourcing behaviour. Farmers reduced reliance on unregulated local markets and neighbours, shifting instead towards local seed multipliers and informed seed recycling practices. While recycling remains common due to cost and liquidity constraints, YWQC participants recycled for fewer seasons, indicating improved awareness of quality risks. Land allocation patterns further suggest that youth and women increasingly view beans and rice as viable, market-oriented enterprises, even under shrinking landholdings. Overall, the pilot demonstrates that locally anchored, integrated centres can catalyse inclusive seed system transformation when skills development, behavioural change, and institutional partnerships are combined. For scaling, the brief underscores the need to treat YWQCs as a holistic package, align them with national seed and extension policies, Brief strengthen business and financing models, and maintain rigorous gender- and age-responsive monitoring. If institutionalised within district and national strategies, YWQCs offer a practical and scalable pathway to expand quality seed access while advancing youth employment and women’s economic empowerment across Uganda’s seed systems.